THE CONSTITUTIONAL COURT RULING ON THE AUTHORITY OF DSN-MUI IN ISLAMIC FINANCIAL INSTITUTIONS IN INDONESIA - Supyadillah, Asep; Nurhasanah, Nurhasanah; Putri, Novita Akria (Kanun Jurnal Ilmu Hukum, 2025)
The authority of the National Sharia CouncilIndonesian Ulema Council (DSN-MUI) in issuing fatwas in the field of Islamic finance is often perceived as problematic in terms of the legitimacy of MUI as the authorized body to determine sharia aspects within the national legal system. This issue is reflected in Decision Number 65/PUU-XIX/2021 regarding the judicial review of Law Number 21 of 2008 on Sharia Banking and Decision Number 100/PUU-XX/2022 concerning the judicial review of Law Number 19 of 2008 on State Sharia Securities (SBSN), both of which challenge MUIs position in issuing sharia fatwas. This study employs a doctrinal method with a philosophical approach and the analysis of the theory of the positivization of law. This approach is used to examine how philosophical foundations and the construction of positive law place DSN-MUI within the structure of legal authority in Indonesia. The findings show that the Constitutional Court consistently rejected the petitioners claims and affirmed the status of MUI as the legitimate Islamic religious authority responsible for ensuring legal certainty in the administration of Islamic finance. This strengthens the legitimacy of DSN-MUI in both sharia banking and SBSN instruments and highlights its role in harmonizing religious norms with positive law. This clarifies the position of DSN-MUI within Indonesias legal system while providing an academic foundation for the development of Islamic finance regulations that are more certain, integrated, and aligned with both legal practice and national legal development.